2015
DOI: 10.1007/s12975-015-0403-0
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers Related to Carotid Intima-Media Thickness and Plaques in Long-Term Survivors of Ischemic Stroke

Abstract: Lifestyle risk factors, inflammation and genetics play a role in the development of atherosclerosis. We therefore studied Fc gamma receptor (FcγR) polymorphisms, interleukin (IL)-10 polymorphisms and other biomarkers related to carotid intima-media thickness (cIMT) in patients with ischemic stroke at a young age. Patients were evaluated 12 years after stroke occurrence. Patients (n = 232) 49 years of age or younger with an index stroke between 1988 and 1997 were retrospectively selected. Blood samples were tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Using carotid ultrasound, Ulrike et al . showed that HbA1c was an independent risk factor for cIMT in long-term survivors of ischemic stroke 26 . Comparing with carotid ultrasound, MRI can accurately characterize plaque morphology and tissue composition of human carotid atherosclerotic plaque 27 .…”
Section: Discussionmentioning
confidence: 98%
“…Using carotid ultrasound, Ulrike et al . showed that HbA1c was an independent risk factor for cIMT in long-term survivors of ischemic stroke 26 . Comparing with carotid ultrasound, MRI can accurately characterize plaque morphology and tissue composition of human carotid atherosclerotic plaque 27 .…”
Section: Discussionmentioning
confidence: 98%
“…As the leading cause of death, ischemic stroke (>80% of stroke) is a medical emergency with high morbidity and mortality (1,2). It causes multiple pathophysiological events including mitochondrial response, excitotoxicity, protein misfolding and immune response, which lead to the delayed neuronal loss (3).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that the level of HbA1c was associated with carotid IPH, which was a primary characteristic of vulnerable plaques. Previous studies have identi ed the association between HbA1c and subclinical atherosclerosis, suggesting that HbA1c may be involved in the early stage of atherosclerosis (4,5,16,17). As the development of atherosclerosis, the rupture of vulnerable carotid plaques could result in ischemic stroke (1).…”
Section: Discussionmentioning
confidence: 99%